2002
DOI: 10.1073/pnas.202463999
|View full text |Cite
|
Sign up to set email alerts
|

A dominant-negative MEC3 mutant uncovers new functions for the Rad17 complex and Tel1

Abstract: The Rad17-Mec3-Ddc1 complex is essential for the cellular response to genotoxic agents and is thought to be important for sensing DNA lesions. Deletion of any of the RAD17, MEC3 or DDC1 genes abolishes the G 1 and G2 and impairs the intra-S DNA-damage checkpoints. We characterize a dominant-negative mec3-dn mutation that has an unexpected phenotype. It inactivates the G1 checkpoint while it leaves the G2 response functional, thus revealing a difference in the requirements of the DNA-damage response in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
1
11
1
Order By: Relevance
“…Rad53 activation requires prior hyperphosphorylation of Rad9. This event is Mec1 dependent and can be observed in response to any kind of damage, both in G1 and G2, where Rad9 is already modified at a basal level (Emili, 1998; Sun et al , 1998; Vialard et al , 1998; Giannattasio et al , 2002). We compared the status of Rad9 after 4NQO treatment in wt and in cells lacking RAD14 or RAD2 , a gene coding for a factor of the structure‐specific endonuclease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rad53 activation requires prior hyperphosphorylation of Rad9. This event is Mec1 dependent and can be observed in response to any kind of damage, both in G1 and G2, where Rad9 is already modified at a basal level (Emili, 1998; Sun et al , 1998; Vialard et al , 1998; Giannattasio et al , 2002). We compared the status of Rad9 after 4NQO treatment in wt and in cells lacking RAD14 or RAD2 , a gene coding for a factor of the structure‐specific endonuclease.…”
Section: Resultsmentioning
confidence: 99%
“…It is still unclear how Mec1 and its substrates are brought in close proximity onto DNA after genotoxic treatment. It has been recently shown that Mec1–Ddc2 and the PCNA‐like complex can be independently recruited onto damaged DNA (Kondo et al , 2001; Melo et al , 2001; Zou et al , 2002), and it has been suggested that the PCNA‐like complex might be involved in recruiting different substrates for Mec1 (Giannattasio et al , 2002; Zou et al , 2002). Critical Mec1 targets are Rad9 and Rad53; their modification allows these two proteins to interact, leading to Rad53 kinase activation.…”
Section: Introductionmentioning
confidence: 99%
“…4). This residual response may operate through clamp-Tel1 interactions (Giannattasio et al, 2002). Finally, damage sensitivity measurements of the mutants lends additional support to a model that direct activation by 9-1-1 and indirect activation by 9-1-1 via Dpb11 contribute to checkpoint function in G2/M.…”
Section: Resultsmentioning
confidence: 99%
“…In S. cerevisiae, Mec1 plays a primary role in sensing and transducing checkpoint signals in response to different types of DNA lesions, while Tel1 functions in the DNA damage response are inferred from the finding that its absence increases the sensitivity of mec1 mutants to genotoxic agents (62,84), it impairs the checkpoint response to phleomycin treatment during S phase (67), and it allows the G 2 /M transition after DNA damage in a dominant-negative MEC3 mutant (29). Moreover, altering DSB processing in mec1⌬ cells by deletion of SAE2 or non-null mutations in the RAD50 and MRE11 genes triggers Tel1/MRX-dependent Rad53 phosphorylation and interaction with Rad9 after MMS and hydroxyurea treatment, suggesting that accumulation of DNA lesions that specifically activate Tel1 might take place under these conditions (104).…”
Section: Discussionmentioning
confidence: 99%
“…Although TEL1 deletion by itself does not confer sensitivity to DNA-damaging agents, Tel1 functions in the DNA damage response are inferred from the finding that its absence increases the sensitivity of mec1 mutants to genotoxic agents (62,84), and it impairs the checkpoint response to phleomycin treatment during S phase (67). Tel1 is also responsible for the G 2 arrest after DNA damage in a dominant-negative MEC3 mutant (29). Moreover, TEL1 overexpression can suppress both cell lethality and hypersensitivity to DNA-damaging agents of mec1⌬ and ddc2⌬ mutants, indicating that excess Tel1 can bypass the requirements for the Mec1-Ddc2 complex (11,84).…”
mentioning
confidence: 99%